Health Education On Balanced Nutrition in Toddlers in Teluk Pinang Village - Nina Yusnia; Citra Resmi Lestariana Putri (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Introduction: Knowledge of balanced nutrition in toddlers in Indonesia is still relatively low. Of the 37.2% of toddlers in Indonesia, only 13.0% experienced malnutrition status based on age and 2.5% who experienced thinness based on weight compared to height. This means that there are only 13.0% and 2.5% of children under five who have been malnourished from a long time until now, low balanced nutrition knowledge has resulted in Indonesia still facing nutritional problems in toddlers such as malnutrition. Purpose: To determine the effect of